\ - Rizaldi, Muhammad; Irianto, Zaitun Qamariah (Educativo: Jurnal Pendidikan, 2023)
The aim of this research was to provide an overview of students' perceptions of teaching as a graduate career in the English study program at IAIN Palangka Raya. A quantitative survey research approach was used, with a population sample of 55 students obtained using the Total Sampling Technique. Data were collected by a questionnaire, which was then analyzed using SPSS version 26.0. The results demonstrated a favorable perception, with a score of 79% and the Agree category. The majority of participants expressed positive opinions toward the development and flexibility of a graduate career, including becoming a teacher, as provided by IAIN Palangka Raya's English Education Study Program.